2018
DOI: 10.17582/journal.jahp/2018/6.4.96.102
|View full text |Cite
|
Sign up to set email alerts
|

Blood Metabolic Profile of Lambs Fed Complete Diet Supplemented with Exogenous Fibrolytic Enzymes Cocktail

Abstract: Blood metabolic profile (BMP) serve as clinical indicators for the impact of dietary manipulations on physiological health status. The present study was undertaken with the aim to assess the effect of in-feed supplementation of exogenous fibrolytic enzymes (EFE) cocktail as feed additive on BMP in lambs. Crossbred lambs (n=12) of 4-6 months age were distributed into two groups of 6 animals each and fed for a period of 90 days followed by 6 days metabolism trial. Animals in both the groups were offered complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 2 publications
13
6
0
Order By: Relevance
“…Most of the blood count parameters were not affected by the treatment, except for some WBC parameters. The same response was observed by Beigh et al [37] in their study with lambs fed a cocktail of exogenous fibrolytic enzymes and/or Artemisia absinthium L. (known as wormwood herb), and by Morsy et al [38], who used red propolis extract with antioxidant characteristics to feed Santa Ines ewes; their results showed that the extract or even the plant itself in the diet increased the number of leukocyte counts.…”
Section: Health Parameterssupporting
confidence: 74%
“…Most of the blood count parameters were not affected by the treatment, except for some WBC parameters. The same response was observed by Beigh et al [37] in their study with lambs fed a cocktail of exogenous fibrolytic enzymes and/or Artemisia absinthium L. (known as wormwood herb), and by Morsy et al [38], who used red propolis extract with antioxidant characteristics to feed Santa Ines ewes; their results showed that the extract or even the plant itself in the diet increased the number of leukocyte counts.…”
Section: Health Parameterssupporting
confidence: 74%
“…The RBC level of the sheep in the study was 12.11±2.18 (x10 6 /µL), which was still in the normal limit according to the textbook (Byers and Kramer, 2010) that was 9.00-15.00 x10 6 /µL. It was consistent with the study of the sheep with CF supplementation in Exogenous Fibrinolytic Enzymes Cocktail (Beigh et al, 2018). The hemoglobin parameter of the sheep in the study were 12.40±1.96 (g/dL), which was consistent with the textbook was 9.00-15.00 g/dL (Byers and Kramer, 2010) and it was corroborated by Anbarasu et al(2002) who conducted a study of the sheep with the basal feed of wheat straw (10.50 to 11.62 g/dL).…”
Section: Resultssupporting
confidence: 86%
“…The MCV parameter of the sheep in the study was 30.46±3.38 fL that was considered to be in the normal limit of the textbook parameter (Byers and Kramer, 2010) at level 28.00-40.00 fL and consistent with the MCV of the sheep reported by Saeed et al(2019), which was at the level of 29.40±0.33 fL and also the MCV of the sheep with the CF supplemented with Exogenous Fibrinolytic Enzymes Cocktail, which was at the level of 27.00±0.25 fL (Beigh et al, 2018). The normal MCV parameter of the sheep in the study was consistent with the study of the sheep fed with Moringa oleifera leaf meal by (Jiwuba et al, 2016).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Measuring of gene expression and blood metabolites levels is a reliable method for evaluation sheep growth performance and health status in addition to it is a useful way for judging of individual animal physiological status, diagnosis of metabolic disorders, clinical nutritional balances, deficit condition, treatment monitoring and prognostics (Nath et al, 2014;Beigh et al, 2018). The mortality of pre-and post-weaning lambs, lower growth rates, and lack of feed are major problems facing most sheep farmers and they are main factors which have a negative effect on total productivity in sheep husbandry and represents an economic loss (Saleem et al, 2017;Elshazly and Youngs, 2019).…”
Section: Introductionmentioning
confidence: 99%